Analisis Hukum Bayi Tabung dalam Perspektif Hukum Islam Dan Hukum Positif - Marpaung, Arifin; Harahap, Andrew Hermawan; Nakita, Delvi Salwa; Husaini, Fakhri (Universitas Pahlawan Tuanku Tambusai, 2024)
At the present time the whole world is facing what is called the development of the times, various discoveries have been made by scientists, including advances in science and technology in the world of medicine. One of the factors that is trending now is dealing with unnatural births using the IVF system by means of Artificial insemination, this can be seen as a way to solve problems for married couples who have been waiting for a child for a long time. However, from the other side, the IVF program raises various legal problems, especially in Islamic law and positive law in Indonesia. Marriage is not just a biological outlet, but contains noble elements that will be achieved in it. One of the goals of marriage is to produce offspring.